2020
DOI: 10.3390/app10155146
|View full text |Cite
|
Sign up to set email alerts
|

Solutions to Increase PV Hosting Capacity and Provision of Services from Flexible Energy Resources

Abstract: Future smart grids will be more dynamic with many variabilities related to generation, inertia, and topology changes. Therefore, more flexibility in form of several active and reactive power related technical services from different distributed energy resources (DER) will be needed for local (distribution network) and whole system (transmission network) needs. However, traditional distribution network operation and control principles are limiting the Photovoltaic (PV) hosting capacity of LV networks and the DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…In the previous studies [2]- [4], in order to increase DER hosting capacity and avoid curtailment of PV active power P, QU-droop has been used as a primary voltage control method, and P curtailment by PU-droop control as a secondary method. In [4], the PV hosting capacity with and without BESS at the same LV network connection point was studied with different DER unit droop settings and HV/MV substation transformer OLTC values.…”
Section: A Local Der Control Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previous studies [2]- [4], in order to increase DER hosting capacity and avoid curtailment of PV active power P, QU-droop has been used as a primary voltage control method, and P curtailment by PU-droop control as a secondary method. In [4], the PV hosting capacity with and without BESS at the same LV network connection point was studied with different DER unit droop settings and HV/MV substation transformer OLTC values.…”
Section: A Local Der Control Methodsmentioning
confidence: 99%
“…In the previous studies [2]- [4], in order to increase DER hosting capacity and avoid curtailment of PV active power P, QU-droop has been used as a primary voltage control method, and P curtailment by PU-droop control as a secondary method. In [4], the PV hosting capacity with and without BESS at the same LV network connection point was studied with different DER unit droop settings and HV/MV substation transformer OLTC values. Based on the studies, it was concluded in [4] that flexible weekly/monthly/seasonal and coordinated QU-, PU-and Pf-droop settings (with dead-zones) are needed on LV network-connected PVs and BESSs in order to improve their flexibility services provision.…”
Section: A Local Der Control Methodsmentioning
confidence: 99%
See 3 more Smart Citations